The Roman Municipium of Urvinum Hortense. Preliminary data and reflections on local pottery* - Cecconi , Niccolò; Sciaramenti, Benedetta (O T I V M, 2021)
After introducing the history of the Umbrian Municipium Urvinum Hortense, and briefly examining the archaeological evidence and the site’s topography, this contribution presents the results of an investigation concerning two aspects of craft production in the ancient Roman city. The first concerns the exploitation of raw materials, in particular the rock vein and clay of the hill where the city was erected. The second regards the formal aspects and the specific ways in which locally produced ceramic artefacts were used, all discovered during the excavations conducted by the University of Perugia between 2017 and 2019. ————————- (*)The materials published in this article come from the ongoing archaeological excavation of Urvinum Hortense (Collemancio di Cannara - Pg), Scientific Direction of G.L. Grassigli (Full Professor - Classical Archeology - UniPg) granted to the Municipality of Cannara, prot. 16005 del 10.06.2019, by the Soprintendenza ABAP - Umbria and the Direzione Generale ABAP.